(untitled) (Journal of Plant Disease Sciences, 2019)
Field experiments were conducted at Rice Research Station, Moncompu, Alappuzha during Rabi, 2012-13, Kharif, 2013, Rabi, 2013-14 and Rabi, 2014-15 with the objective of evaluation of efficiency of newer and commercially available fungicides against false smut disease of rice. The fungicides evaluated at the time of panicle emergence stage against false smut disease of rice. The efficacy of two best chemicals were evaluated further in the six farmer’s field of different Kuttanad region during Rabi, 2015-16. The fungicidal spray was tested at two different crop stages (Panicle emergence and 50% flowering stage) to identify the correct time of application for the control of false smut disease. The farm trial results showed that the application of contact fungicide Copper hydroxide 77 WP @ 2.0 g/l at the time of 50% flowering stage (or) systemic fungicide Propiconazole 25 EC @ 1ml/l at the time of panicle emergence was found effective against false smut disease. The results indicated that the above two fungicides were significantly reduced the false smut disease when its applied in two different stages of the crop.